The Paradox of Progress: Energy, Emissions, and the Human Development Index in Bangladesh - Pande, Saikat; Thaker, Siddharth C. (Journal of Environmental and Energy Economics, 2025)
As one of the world's most climate-vulnerable and rapidly developing nations, Bangladesh faces the urgent task of advancing human development while addressing environmental damage. Designing effective policy requires a clear understanding of what drives its Human Development Index (HDI). This study investigates the dynamic effects of carbon dioxide (CO2) emissions, electricity access, nitrous oxide (N2O) emissions, and population on the HDI in Bangladesh using data from the World Bank from 1991 to 2023. By using the ARDL bounds testing method, a stable long-run cointegrating relationship was confirmed. The long-run findings are cross-checked for robustness using FMOLS, DOLS, and CCR. This study finds that in the long run, a 1% increase in emissions corresponds to a 0.33% rise in the HDI, showing that development continues to rely on carbon-intensive activities. However, the study also finds that a 1% increase in electricity access is linked to a 0.13% fall in the HDI. This suggests that the environmental externalities of the current fossil-fuel-dependent energy infrastructure may be harming the overall quality of life. The short-run dynamics are complex, characterized by oscillating effects from the explanatory variables and an extremely rapid adjustment to equilibrium (ECT = -0.990). Policy efforts should therefore focus on decoupling human development from emissions by accelerating the transition to renewable energy, enhancing energy efficiency, and promoting sustainable agricultural practices. These insights are vital for guiding Bangladesh toward achieving its Sustainable Development Goals (SDGs 3, 4, 7, and 13) and can serve as a model for other developing nations navigating similar challenges. By implementing evidence-based policies, Bangladesh can achieve balanced development, positioning the country as a leader in sustainable development within the region.